Gender difference in plasma fatty-acid-binding protein 4 levels in patients with chronic obstructive pulmonary disease. Issue 1 (29th February 2016) - Zhang, Xue; Li, Diandian; Wang, Hao; Pang, Caishuang; Wu, Yanqiu; Wen, Fuqiang
Abstract : Plasma FABP4 levels were higher in females with COPD compared with both males with COPD and healthy females. FABP4 levels correlated inversely with lung function, and positively with adiponectin and TNFα in COPD. Abstract : COPD (chronic obstructive pulmonary disease) is characterized by airway inflammation and increases the likelihood of the development of atherosclerosis. Recent studies have indicated that FABP4 (fatty-acid-binding protein 4), an intracellular lipid chaperone of low molecular mass, plays an important role in the regulation of inflammation and atherosclerosis. We carried out a preliminary clinical study aiming at investigating the relationships between circulating FABP4 levels in patients with COPD and inflammation and lung function. We enrolled 50 COPD patients and 39 healthy controls in the study. Lung function tests were performed in all subjects. Plasma levels of FABP4 and adiponectin, TNFα (tumour necrosis factor α) and CRP (C-reactive protein) were measured. The correlations between FABP4 and lung function, adipokine (adiponectin), inflammatory factors and BMI (body mass index) were analysed. Compared with both males with COPD and healthy females, plasma FABP4 levels in females with COPD were significantly increased. Adiponectin and CRP levels were significantly higher in patients with COPD. Furthermore, we found that FABP4 levels were inversely correlated with FEV1 % predicted (FEV1 is forced expiratory volume in 1 s) and positively correlated with adiponectin and TNFα in COPD patients. In addition, a positive correlation between plasma FABP4 and CRP was found in females with COPD. However, FABP4 levels were not correlated with BMI. Our results underline a gender difference in FABP4 secretion in stable COPD patients. Further studies are warranted to clarify the exact role of FABP4 in the pathogenesis of COPD.